Measuring Strengths, Opportunities, Aspirations, and Results: Psychometric Properties of the 12-Item SOAR Scale - Cole, Matthew L.; Stavros, Jacqueline M.; Cox, John; Stavros, Alexandra (Frontiers in Psychology, 2022)
SOAR is a strengths-based framework for strategic thinking, planning, conversations, and leading that focuses on strengths, opportunities, aspirations, and results. The SOAR framework leverages and integrates Appreciative Inquiry (AI) to create a transformation process through generative questions and positive framing. While SOAR has been used by practitioners since 2000 as a framework for generating positive organizational change, its use in empirical research has been limited by the absence of reliable and valid measures of SOAR. We report on the reliability, construct validity, and measurement invariance of the SOAR Scale, a 12-item self-report survey organized into four first-order factors (Strengths, Opportunities, Aspirations, Results). Data from a sample of 285 U.S. professionals were analyzed in Mplus using exploratory and confirmatory factor analysis structural equation modeling. The Four-Factor First-Order ESEM model had the best model fit. Measurement invariance tests found scalar invariance of the SOAR Scale across gender and education groups. Implications are discussed for using the SOAR Scale to build resilience at the individual, team, and organization level.